(untitled) (Medico Legal Update, 2021)
This aims of the study to identify spatial microsplastic pollution sediments in the Tallo River Makassar City. This type of research is descriptive observational. This research design uses a Geographical Information System (GIS) Statistical analysis using the average abundance of microplastics is presented in tables and graphs, then analyzed descriptively quantitatively at each station. Data showing the mean ± standard deviation were analyzed using SPSS software. Based on the results of research that has been done, the number of microplastics found in the sediments in the Tallo River is 289. The highest microplastic size found in the Tallo River sediments is 1.00-4.75 mm as much as 167 MP (58%) with an average abundance of 18, 56 ± 30,875 MP/kg. Followed by a size of <1 mm as much as 112 MP (39%) with an average abundance of microplastics 12.44 ± 17.686 MP/kg and sizes> 4.75 mm as much as 10 MP (3%) with an average abundance of microplastics 1.11 ± 2,315 MP/kg.